Implementasi Nilai Budaya Lokal dalam Pembentukan Karakter Siswa - Marhan Ntai; Nina Lamatenggo; Besse Marhawati (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to describe the implementation of local cultural values in shaping students’ character at SD Negeri 1 Telaga Biru, Gorontalo Regency. The study focuses on the philosophy of Adati Hula-hula’a to Syara’a, Syara’a Hula-hula’a to Quru’ani and the cultural value of Huyula (mutual cooperation). This research employed a qualitative approach using a case study design. Data sources consisted of the principal, classroom teachers, and Islamic education teachers. Data were collected through interviews, observations, and documentation. The findings reveal that the implementation of local cultural values was carried out through religious habituation, exemplary attitudes, classroom learning, and social activities. The strategies implemented by the school included integrating cultural values into the school vision and mission, routine religious activities, and collaborative social programs. The study also found that local cultural values contributed significantly to the development of students’ religious attitudes, discipline, honesty, social care, responsibility, politeness, and cooperation. Therefore, local culture-based character education is considered effective in fostering holistic student development in elementary schools.